Active posterior pelvic tilt range of motion is decreased in soccer players with chronic groin pain: A case-control study - Stevenson, K.; Bleakley, C.; Tak, I. J. R.; Langhout, R. F. H.; Saligari, R.; Glasgow, P. (Translational Sports Medicine, 2020)
The purpose of this case control study was to examine the effect of groin pain status on active posterior pelvic tilt range of motion in soccer players. 66 semi-professional male soccer players were recruited and sub grouped by: chronic groin pain (GP, n = 16), history chronic groin pain (HxGP, n = 16), no history of chronic groin pain (NoGP, n = 32). Blinded outcomes measures were: active posterior pelvic tilt range of motion (PPT ROM) undertaken in dominant and non-dominant weight bearing, and hip flexor length. A one-way ANOVA (P <= .05) examined the main effects of injury group (3 levels: GP, HxGP, NoGP), followed by post hoc tests with bonferroni correction. Results showed that PPT ROM was significantly lower in the GP group compared to HxGP (MD 2.8º; 95% CIs 0.2-5.5º, P = .03) and NoGP groups (MD 4.9º; 95% CIs 2.7-7.3º, P < .0001). The differences between HxGP and NoGP groups were not significant (MD 2.1º; 95% Cis -.19 to 4.4, P = .08) and the relationship between hip flexor length and PPT ROM was weak. In conclusion, active PPT ROM was decreased in athletes with chronic groin pain compared to injury free controls. Although we cannot conclude a causal relationship, restoration of active PPT should play a role in the management of athletes with groin pain.